Efektifitas Sargassum Plagyophullum dan Gracilaria Verrucosa dalam Menurunkan Kandungan Amonia, Nitrit dan Nitrat dalam Air Tambak - Izzati, Munifatul (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2010)
Ammonia, nitrite and nitrate accumulation in shrimp pond is a big problem for shrimp survival, since these compunds are toxic. We propose to solve the problem by addition of seaweeds, Sargsasum plagyophyllum and Gracilaria verrucosa to reduce ammonia, nitrite and nitrate. The aim of this research is to evaluate the effectivity of Sargassum and Gracilaria in reducing ammonia, nitrite and nitrate content in the water. This research was conducted in brackish water shrimp pond, using 1m x 1m x 1.2m plastic enclosures as models. Plastic enclosures without seaweeds were served as controls. All treatments were repeated 4 times. We observed the reduction of ammonia, nitrite and nitrate content weekly. Results indicated that both sargassum and Gracilaria were capable in reducing this inorganic nitrogen content. However, Gracilaria was more effective in the role of ammonia, nitrite and nitrat reduction compared to Sargassum.